2005
DOI: 10.1007/s10800-004-3462-6
|View full text |Cite
|
Sign up to set email alerts
|

High capacity supercapacitors based on modified activated carbon aerogel

Abstract: Carbon aerogel derived from a modified resorcinol-formaldehyde (RF) method without supercritical drying step was activated under CO 2 flow and further modified with a surfactant sodium oleate solution. Carbon aerogel, activated carbon aerogel (ACA) and modified activated carbon aerogel (MACA) were characterized by Brunaver, Emmett and Teller(BET) surface measurement, constant-current charge-discharge and cyclic voltammetry(CV). It was found that the specific surface area of the ACA was twice that without activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 10 publications
1
40
0
Order By: Relevance
“…This technology has attracted great interest [4][5][6][7][8] and several VRB systems for practical application have been demonstrated. A VRB system with 4 MW/ 6 MWh has been installed at a wind power station in Tomamae, Hokkaido, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has attracted great interest [4][5][6][7][8] and several VRB systems for practical application have been demonstrated. A VRB system with 4 MW/ 6 MWh has been installed at a wind power station in Tomamae, Hokkaido, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous preliminary study has shown that the hydropobisation of carbonaceous materials can be improved by the attachment of hydrophobic moiety of surfactant sodium oleate (OAS) [19], and as results, the affinity of carbon materials toward and the wettability in non-aqueous electrolyte solution based on PC solvent has been improved, resulting in enhanced performance of EDLCs [20]. However, the improvement in the performance of EDLCs by surface modification with OAS is relatively limited, primarily attributable to the limited hydrophobisation of carbon surface due to the existence of remaining hydrophilic functional groups (i.e., hydroxyl) after the modification.…”
Section: Introductionmentioning
confidence: 99%
“…The development of electrochemical supercapacitors (ES) is the subject of intense experimental and theoretical work [1][2][3][4][5]. This research focuses on advanced materials, new fabrication technologies, design and modeling.…”
Section: Introductionmentioning
confidence: 99%